Treatment modalities in breastfeeding babies with marasmus and kwashiorkor associated with ankyloglossia - Asti Praborini; Ratih Ayu Wulandari; Okky Nafiriana (Indonesian Journal of Perinatology, 2023)
Introduction: Successful breastfeeding depends on an infant's ability to latch onto the mother's breast correctly. A poor latch will cause insufficient milk transfer which will cause poor growth. Each type of mammal produces different components of milk which make it species-specific and adjusts to their needs, growth rate, and breastfeeding habits. Human breast milk has many benefits for human babies because it contains various substances both nutrition and protection. This study aims to present two infants who suffered from Ankyloglossia, which hindered the baby's ability to breastfeed and eat solid food Case Presentation: The study presented two infants who suffered from Ankyloglossia, which hindered the baby's ability to breastfeed and eat solid food. These babies were diagnosed with marasmus and kwashiorkor. After revision on both the lip- and tongue ties, supplementation with pasteurized human milk donor, and good complementary feeding, the babies finally reach optimal growth and development. Conclusion: The sucking ability of the baby during early breastfeeding was proven to be important and should be examined, to achieve further successful breastfeeding.